Altitudinal biodiversity patterns of seed plants along Gongga Mountain in the southeastern Qinghai–Tibetan Plateau. Issue 17 (7th August 2019) - Zu, Kuiling; Luo, Ao; Shrestha, Nawal; Liu, Bo; Wang, Zhiheng; Zhu, Xiangyun
Abstract: The mechanisms underlying elevation patterns in species and phylogenetic diversity remain a central issue in ecology and are vital for effective biodiversity conservation in the mountains. Gongga Mountain, located in the southeastern Qinghai–Tibetan Plateau, represents one of the longest elevational gradients (ca. 6, 500 m, from ca. 1, 000 to 7, 556 m) in the world for studying species diversity patterns. However, the elevational gradient and conservation of plant species diversity and phylogenetic diversity in this mountain remain poorly studied. Here, we compiled the elevational distributions of 2, 667 native seed plant species occurring in Gongga Mountain, and estimated the species diversity, phylogenetic diversity, species density, and phylogenetic relatedness across ten elevation belts and five vegetation zones. The results indicated that species diversity and phylogenetic diversity of all seed plants showed a hump‐shaped pattern, peaking at 1, 800–2, 200 m. Species diversity was significantly correlated with phylogenetic diversity and species density. The floras in temperate coniferous broad‐leaved mixed forests, subalpine coniferous forests, and alpine shrublands and meadows were significantly phylogenetically clustered, whereas the floras in evergreen broad‐leaved forests had phylogenetically random structure. Both climate and human pressure had strong correlation with species diversity, phylogenetic diversity, and phylogenetic structure of seed plants. Our results suggest that the evergreen broad‐leaved forests and coniferous broad‐leaved mixed forests at low to mid elevations deserve more conservation efforts. This study improves our understanding on the elevational gradients of species and phylogenetic diversity and their determinants and provides support for improvement of seed plant conservation in Gongga Mountain. Abstract : Gongga Mountain (Mt. Gongga) with a broad elevational gradient (from ca. 1, 000 to 7, 556 m a.s.l.), located between the southeastern edge of the Qinghai–Tibetan Plateau (QTP) and the Sichuan Basin, is one of the highest mountains in Himalaya–Hengduan Mountains region and Southwest China and has been recognized as one of the global biodiversity hotspots. Mt. Gongga can be regarded as a "natural laboratory" for studying the ecological and evolutionary drivers of species and phylogenetic diversity.